Nutritional knowledge, family income, and blood sugar level among diabetic patients - Maleki, Mohsen; Payandeh, Abolfazl; Seraji, Maryam; Taherkhani, Mahshid; Bolouri, Ahmad (Intelektual Pustaka Media Utama, 2023)
Nutritional literacy related to diabetes control can play an important role in glycemic control and the reduction of complications of type 2 diabetes. This study aimed to investigate the relationship between nutritional knowledge and hemoglobin A1C (HbA1c). In this study, nutritional literacy and its components (food portion, nutritional content, healthier food choice, and food label reading skill) were evaluated by a valid and reliable questionnaire designed in Singapore for the evaluation of diabetes-related nutrition knowledge. Furthermore, family income, level of education, type of ethnicity, having a smartphone, as well as access to social media of 64 type 2 diabetic patients were assessed. Pearson’s Correlation coefficient between HbA1c and total nutritional knowledge score was calculated at -0.58, which was significant (p<0.001). Participants scored 48%, 55%, 51%, 52%, and 52% of total score for food portion and sizes, nutrition content of food, healthier food choices and safety, food label reading, and overall, respectively. After controlling for possible confounding, regression model results suggested nutritional knowledge and family income were two potential predictors of HbA1c. Improving nutrition and media literacy may help reduce blood sugar levels and treatment costs.